Intermediated vs. Direct Sales and a No-Discrimination Rule - Sebastian Wismer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2013)
When sellers join a platform to sell their products, the platform operator may restrict their strategic decisions. In fact, several platform operators impose most-favored treatment or no-discrimination rules (NDRs), asking sellers not to offer better sales conditions elsewhere. In this paper, I analyze a model that allows for an endogenous split-up of consumers between sales channels. Competing sellers might set different prices across channels, depending on the platform tariff and presence of aNDR. I find that the platform operator imposes a NDR if he faces high transaction costs, if seller competition is weak, and if the initial distribution of consumers on channels is strongly skewed. Prohibiting NDRs can have both positive and negative effects on welfare.
Keywords: D40; L42; L81; 330; Intermediation; Platform pricing; No-discrimination rule